(untitled) (Research, Society and Development, 2022)
With the modernization of technology, new virtual forms of violence have emerged and old ways of perpetrating violence against women have been exacerbated with the use of the internet and social networks. This study aimed to investigate the forms of violence against women on the internet. This is an integrative literature review of the electronc databases SciVerse Scopus, Medical Literature Analysis and Retrieval System Online and Scientific Electronic Library Online. The inclusion criteria were publications that occurred in the time span from January 2016 to July 2021, with the descriptors "Violence," "Internet," "Woman," "Gender," "Sexual Violence," "Sexual Harassment," "Intimate Partner Violence," and "Internet and Abuse". As a result of the review, 30 articles were selected. Nine categories of violence against women on the Internet were identified, included in the concept of sexual violence facilitated by technology, in addition to digital dating abuse and cyberbullying. The most commonly addressed categories were digital dating abuse, revenge porn, sexting, and online misogyny. Most of the studies found concluded greater online victimization for women than for men in all categories except cyberbullying.